Exploring Sex-Related Differences in Microglia May Be a Game-Changer in Precision Medicine - Lynch, Marina A. (Frontiers in Aging Neuroscience, 2022)
One area of microglial biology that has been relatively neglected until recently is sexual dimorphism and this is in spite of the fact that sex is a risk factor in several diseases that are characterized by neuroinflammation and, by extension, microglial activation. Why this sexual dimorphism exists is not known but the panoply of differences extend to microglial number, genotype and phenotype. Significantly, several of these sex-related differences are also evident in health and change during life emphasising the dynamic and plastic nature of microglia. This review will consider how age impacts on sex-related differences in microglia and ask whether the advancement of personalized medicine demands that a greater focus is placed on studying sex-related differences in microglia in Alzheimer’s disease, Parkinson’s disease and models of inflammatory stress and trauma in order to make true progress in dealing with these conditions.